Effects of Stabilization Exercises on Pain and Functional Status in Cervical Radiculopathy - Huda Hamid, Saima Riaz, Maria Khan, Sana Hafeez, Rehan Ramzan Khan, Sajid Rashid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to identify the effects of stabilization exercises on pain and functional status in patients of cervical radiculopathy. Methodology: The study was a Quasi experimental trial and was conducted in outpatient department of Ittefaq Hospital Lahore. The patients (n=44), who met the inclusion criteria were divided into 2 groups. Group A (n=22) was treated with stabilization exercises and conventional physical therapy protocol whereas group B (n=22) was given conventional physical therapy protocol only. Patients were evaluated with DASH score and NPRS for functional assessment and pain respectively at baseline and after 3 weeks of treatment in both groups. Data was analyzed on SPSS 21. Results: Mean age of patients in group A (Experimental group) and group B (Conventional group) were 54.22± 4.96 and 51.95±4.21 respectively. Within the group comparison for NPRS and DASH scores were statistically significant with p values <0.05. P values for across the group comparison were 0.40 and <0.05 for DASH and NPRS score respectively. Conclusion: The current study concludes that stabilization exercises along with conventional physical therapy and conventional physical therapy alone, both are effective in improving pain intensity and functional status in patients with cervical radiculopathy. However stabilization exercises are more effective in reducing the pain intensity levels.